Islamic Self-Healing on Increasing Patient Self-Efficacy - Suhaimi Fauzan; Muhammad Ibnu Khatan; Mita Mita; Fauzan Alfikrie; Sulastri Herdaningsih; Herman Herman (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Hemodialysis is one of kidney replacement therapy that is mostly performed by patients with chronic kidney failure. Changes in various physical and psychological conditions that cause CKD patients on hemodialysis will find excessive stressors. One of the alternative and complementary therapies to achieve self-healing is mind body and spirit therapy. The human aspect is an integral part of a number of therapies such as prayer, health, and yoga. Objective: Determine the effect of Islamic self healing n the level of self-efficacy in chronic kidney failure patients undergoing hemodialysis Methods: This research was quasi-experimental  pretest-posttest with control group design. The samples were collected approximately 40 by randomly sampling during 12-26 July 2022. The population in this study was all patients who underwent hemodialysis routinely at a RSUD dr. Soedarso. The self-efficacy was measured by the chronic kidney disease (CKD) self-efficacy instrument: development and psychometric evaluation. The analysis technique in this study was sample paired t test and Mann Whitney test. Result: The results of this study indicate that most of the respondents are female (65%), have an average age of 51 years, and have the last elementary school education as much as 68%. The results of the sample paired t test in the control group were (0.40), the intervention group (0.002). Then the results of the Mann Whitney test on the efficacy value after 4 weeks of intervention showed a sig. 0.000. Conclusion: This can be done with the interdisciplinary involvement of care and psychological teams. It is recommended that spiritual therapy be included in the treatment program by health professionals, included in teaching programs, and used on a personal level for nurses and hemodialysis patients.